Análise da eficiência operacional e definição das áreas de Influência locacionais dos ecopontos de Fortaleza-Ceará - Alexandre, Adriano Ricardo Almeida (2021)
The generation of solid waste is growing in the world and in Brazil, this problem exists in Fortaleza, in the State of Ceará. The large generation of solid waste and clandestine disposal on roads, public and private places originate mainly from the rubble of the civil construction, pruning, cuttings of plant species, as well as voluminous furniture damaged, unusable appliances and other large useless items. through of studies of indicators and the observation of the growing quantity of these deposits clandestine, known as "garbage points", ecopoints are proposed, to attenuate these harmful effects on the daily life of the city. These develop two important programs incentive collection: E-carroceiro and Recicla Fortaleza. This study is dedicated to the evaluation of operational performance of 49 ecopoints by the DEA (Data Envelopment Analisys) model, using the SBM (Slacks-Based Measure) method oriented to outputs (products) with variable scales (SBM-O-V). The efficiencies found by the SBM-O-V model of the classical and inverted boundaries are transformed into composite efficiencies and these in standardized. The normalized efficiencies are scaled from the least efficient to the most efficient, considering four groups, classified as very critical, critical, regular and great, to assist managers in decision making. Another proposed analysis of ecopoints is about its location through the division of the city's geographic space, through the Voronoi Polygons model, using the QGIS computational platform 2.18, where their areas of locational influences are defined without and with physical obstacles. The physical obstacles are made up of rivers, lakes, streams, railways, subway lines and roads with a large flow of vehicles that impede access to ecopoints by users. Without physical obstacles, the average of the calculated areas is 6.75 Km² (kilometers squares) and, with physical obstacles, the average decreases to 5.13 Km². Thematic maps are generated for graphical representations of the influence areas. In the use of obstacles physical, one discovers areas in the city without any influence. It is concluded that the study of Operational and locational influence area analyzes are tools that complement in aiding decision-making by managers about the city's ecopoints from Fortaleza.